Peran Kinerja Keuangan dan Struktur Aset sebagai Prediktor Agresivitas Pajak Emiten Sektor Kesehatan di Indonesia - Reza Arliantari; Pigo Nauli (GEMILANG: Jurnal Manajemen dan Akuntansi, 2026)
This study aims to analyze the effect of profitability, leverage, fixed asset intensity, and liquidity on tax aggressiveness in health sector companies listed on the Indonesia Stock Exchange (IDX) from 2021 to 2024. The sampling method used was purposive sampling with two criteria, namely 1) healthcare companies listed on the Indonesia Stock Exchange (IDX) from 2021 to 2024, 2) health sector companies that disclosed the information needed by researchers from 2021 to 2024, resulting in 35 health companies as research samples with a total of 119 observation data during the four-year observation period. The data analysis technique used was panel data regression using EViews 12 software and SPSS v26. The results showed that profitability did not have a significant effect on tax aggressiveness. Meanwhile, leverage, fixed asset intensity, and liquidity had a significant positive effect on tax aggressiveness. Furthermore, profitability, leverage, fixed asset intensity, and liquidity significantly affect tax aggressiveness. These findings are in line with agency theory, which states that differences in interests between companies and the government can trigger tax aggressiveness.